Introduction - Brymer, Richard A.; Counts, David R. (Anthropologica, 2022)
Sociology and Anthropology developed in the latter part of the 19th century. The development of sociology and anthropology coincided with the rise of an industrial urban society, and the spread of that society, via colonial contact with other cultures at less institutionally complex levels of integration. These two disciplines followed different drummers, with sociologists staying home and observing the development of industrial society, and anthropologists venturing forth to observe the newly contacted smaller scale societies. This empirical difference has had consequences for the kinds of theories that the respective disciplines have developed. In this introduction we will focus on one of these theories — deviance — and how it has and has not developed. First, we briefly review the sociology of deviance, and its narrow base in the industrial world; then we examine the absence of such a body of systematic theory in anthropology and what it might take for deviance. Then, we suggest ways of remedying the problems of both disciplines with a reconciliation and, finally, provide a brief outline of the articles in this volume